Analisis kualitatif bahan kimia obat dalam jamu pegal linu di wilayah kabupaten Grobogan - Azri, Anna Sa'dia; Haresmita, Perdana Priya (Sasambo Journal of Pharmacy, 2024)
The use of traditional medicine in Indonesia, particularly jamu, remains very popular and an important part of the public health culture. According to the 2018 Riskesdas data, around 59.12% of the Indonesian population consumes jamu, and 95.6% of them recognize the health benefits obtained from it. Jamu, which is made from various types of plants, has been used for thousands of years to maintain health and treat various diseases. This study used Thin Layer Chromatography to identify Medicinal Chemicals (BKO) in jamu circulating in Grobogan Regency, Central Java. The purpose of this study was to analyze the content of medicinal chemicals in traditional herbal medicine. Six samples of jamu pegal linu were tested with Silica Gel 60 F254 stationary phase and different mobile phases for each standard. The results showed that all samples of jamu pegal linu tested did not contain the investigated BKOs, indicating product safety from this aspect.